The SH-SY5Y cell line in Parkinson’s disease research: a systematic review - Xicoy, Helena; Wieringa, Bé; Martens, Gerard J.M. (Molecular neurodegeneration, 2017)
Parkinson's disease (PD) is a devastating and highly prevalent neurodegenerative disease for which only symptomatic treatment is available. In order to develop a truly effective disease-modifying therapy, improvement of our current understanding of the molecular and cellular mechanisms underlying PD pathogenesis and progression is crucial. For this purpose, standardization of research protocols and disease models is necessary. As human dopaminergic neurons, the cells mainly affected in PD, are difficult to obtain and maintain as primary cells, current PD research is mostly performed with permanently established neuronal cell models, in particular the neuroblastoma SH-SY5Y lineage. This cell line is frequently chosen because of its human origin, catecholaminergic (though not strictly dopaminergic) neuronal properties, and ease of maintenance. However, there is no consensus on many fundamental aspects that are associated with its use, such as the effects of culture media composition and of variations in differentiation protocols. Here we present the outcome of a systematic review of scientific articles that have used SH-SY5Y cells to explore PD. We describe the cell source, culture conditions, differentiation protocols, methods/approaches used to mimic PD and the preclinical validation of the SH-SY5Y findings by employing alternative cellular and animal models. Thus, this overview may help to standardize the use of the SH-SY5Y cell line in PD research and serve as a future user's guide.